The Digital Revolution in the Bakery Sector: Innovations, Challenges, and Opportunities from Industry 4.0 - Tsega Y. Melesse; Pier Francesco Orrù (Foods)
Industry 4.0 and digitalization are driving a major transformation in the bakery sector. This systematic review examines the latest advancements in digital technologies and platforms within the bakery industry. Innovations such as robotics, automation, blockchain, and wireless sensor networks are currently revolutionizing bakery operations by enhancing production efficiency, enabling real-time monitoring, and ensuring product traceability. Additionally, digital platforms are improving customer interactions through e-commerce, personalized product offerings, and targeted marketing strategies. Digitalization is also contributing to waste reduction, quality control improvement, and data-driven decision-making, leading to optimized inventory management and more efficient production automation. These advancements are fostering stronger customer engagement, resulting in cost savings and increased profitability. However, the sector faces several challenges, including resistance from companies to adopt new technologies, high implementation costs, a shortage of expertise, and concerns about preserving artisanal quality. This review provides valuable insights for researchers, businesses, and industry experts to deepen their understanding of how digitalization is shaping the future of the bakery sector while highlighting emerging opportunities, challenges, and avenues for future research.